Student start-ups the new landscape of academic entrepreneurship - Wright, Mike 1952-; Mustar, Philippe; Siegel, Donald S. 1959- (World scientific series on public policy and technological innovation, 2020)
"There has been a substantial rise in the number of entrepreneurship courses and programs at colleges and universities. Despite the rapid rise of undergraduate entrepreneurship, there have been few academic studies of this phenomenon. Little is known about the antecedents and consequences of these activities. Student Start-Ups: The New Landscape of Academic Entrepreneurship is the first book of its kind on student entrepreneurship. It sets out to provide a structured approach to understanding the development of the phenomenon by synthesizing and offering the best available quantitative data and new case studies from a range of countries and universities. In doing so, they present the evolution of different models of student entrepreneurship with insights and implications for practice, policy and research"--Provided by publisher.